Adaptation in the dogwhelk, Nucella lapillus (L.) - Kirby, Richard Ralph (UCL (University College London), 1992)
The laboratory rearing and physiological energetics of the intertidal gastropod Nucella lapillus were studied to assess the phenotypic consequences of genetic variation, with a view to establishing Nucella as a model organism for the study of the association between genetic composition and habitat. Nucella proved particularly amenable to rearing in the laboratory. Adult size, whether maintained tidally or non-tidally, was achieved within one year from the time of hatching. Tidal or non-tidal conditions though had a significant effect on growth rate; fastest growth occuring in animals reared non-tidally. Growth was modelled by the Bertalanffy growth equation and compared with Scope For Growth based upon physiological mesurements made on juvenile Nucella; the two were found to be in close agreement over the period of early somatic growth. Data from the laboratory studies were used to address the reported association between multi-locus heterozygosity, genotype and fitness. Significant single locus associations with measures of fitness were observed at the Peptidase locus PEP-1. It was concluded that where the number of loci studied is small, investigations should concentrate upon single locus rather than multi-locus relationships. Using laboratory reared juvenile Nucella, phenotypic differentiation and adaptation was assessed across a karyotypic/gene frequency dine and putative environmental gradient. Neighbouring genetically differentiated populations were shown to exhibit a high degree of both morphological (shell shape) and physiological differentiation, putatively suggested to reflect adaptation to temperature and hyperosmotic stress. Extremes of the dine demonstrated morphological variation previously considered characteristic of sheltered and exposed shores. The 'exposed' morph experienced greater salinity stress during aerial exposure and exhibited an enhanced/faster physiological response to hyperosmotic stress. Physiological, morphological and genetic variation were discussed both with respect to the ...